Between Legal Formalism and Welfare Orientation: Maqāṣid-Based Analysis of Waqf Land Exchange Practices in Banyumas - Supani; Enung Asmaya; Asrizal Saiin; Maulana Yusuf; Cecep Soleh Kurniawan (Institut Agama Islam Negeri Curup, 2026)
This study aims to examine the practice of waqf land exchange in Rempoah Village, Baturaden District, Banyumas Regency, and to analyze how such practice is implemented and justified within the framework of Maqāṣid al-Sharīʿah. While previous studies on waqf management have largely emphasized normative legal doctrines and textual interpretations, they have often overlooked the empirical realities and welfare-oriented considerations underlying waqf land exchange at the local level. This research seeks to fill that gap by investigating the socio-legal dynamics of waqf land exchange and assessing whether and how it aligns with the higher objectives of Islamic law. Employing a socio-legal field research approach grounded in Maqāṣid al-Sharīʿah, the study collected data through documentation, direct observation, and in-depth interviews with relevant stakeholders. The data were analyzed using descriptive-analytical methods, supported by triangulation techniques involving data reduction, data display, and conclusion drawing to ensure validity and reliability. The findings reveal that the waqf land exchange in Rempoah Village functions not merely as a formal administrative procedure, but as a welfare-oriented mechanism designed to optimize the social, economic, and functional benefits of waqf assets for the community. The practice reflects a contextual application of Islamic legal principles in which legal formalism interacts dynamically with considerations of public welfare. Academically, this case contributes to the development of Maqāṣid-based jurisprudence in the field of waqf by demonstrating that Maqāṣid al-Sharīʿah serves as an adaptive and responsive legal framework capable of addressing contemporary socio-economic challenges in waqf governance.